2020
DOI: 10.1016/j.cell.2020.11.019
|View full text |Cite
|
Sign up to set email alerts
|

The Identity of Human Tissue-Emigrant CD8+ T Cells

Abstract: Lymphocyte migration is essential for adaptive immune surveillance. However, our current understanding of this process is rudimentary, because most human studies to date have been restricted to immunological analyses of blood and various tissues.We used an integrated approach to characterize tissue-emigrant immune cells in thoracic duct lymph (TDL). The prevalent immunocytes in human and non-human primate efferent lymph were T cells. Cytolytic CD8 + T cell subsets with effector-like epigenetic and transcriptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 73 publications
7
60
0
Order By: Relevance
“…The edit distance results further show that blood-derived TCR clones segreagate distinct from clones in tissue sites. A recent study also showed that memory CD8 + T cell clones in blood were distinct from those circulating through the lymphatics which could transit through tissues [ 50 ]. Promoting TRM-mediated protection in mouse models requires site specific, rather than systemic priming [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The edit distance results further show that blood-derived TCR clones segreagate distinct from clones in tissue sites. A recent study also showed that memory CD8 + T cell clones in blood were distinct from those circulating through the lymphatics which could transit through tissues [ 50 ]. Promoting TRM-mediated protection in mouse models requires site specific, rather than systemic priming [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of consensus might be partially driven by differences in epitope filtering and/or ranking between the different teams and suggest that efforts to harmonize neoantigen-prediction will be necessary for future clinical cross-comparison of neoantigen-based TIL trials between different centres. 92 Moreover, despite mutations that poorly bind to HLA-II being positively selected for during tumorigenesis, thus emphasising the importance of CD4 + T cells in anti-tumour immunity, 93 the computational prediction and analysis of HLA-II remains an ongoing challenge owing to the highly polymorphic nature of the HLA-II and poorly characterised endosomal HLA-II peptide processing, which limits the development of HLA-II peptide processing algorithms. 45 , 94 , 95 Furthermore, despite the core binding motif of both HLA molecules comprising peptides of approximately nine amino acids, HLA-II-restricted ones have a wider length range (11–20 amino acids) compared with HLA-I-restricted ones (8–11 amino acids) 96 which can make bioinformatics prediction task challenging.…”
Section: Cancer Genomicsmentioning
confidence: 99%
“…Moreover, the expression of various genes involved in CD8 + T cell cytotoxicity, such as those encoding other granzymes and the death receptors Fas and TRAIL, were similarly lower in the lymph node CD8 + T cells from ECs. Recently, HIV-specific CD8 + T cells with a noncytotoxic T TM phenotype were detected more frequently in the thoracic ducts than in the blood ( 435 ).…”
Section: (X) Approaches To Identify Cafmentioning
confidence: 99%